2005
DOI: 10.1620/tjem.205.231
|View full text |Cite
|
Sign up to set email alerts
|

Health Characteristics of Elderly Japanese Requiring Care at Home

Abstract: The number of elderly subjects requiring care is rapidly increasing, however, their health status has not been well studied. The purposes of this study were to describe the health characteristics of the elderly at home who were using long-term care insurance, and to clarify factors that influence dependence for activities of daily living (ADL). The subjects were 194 elderly people living at home, who were approved for care. The items surveyed were the demographic characteristics, care level (or level of depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Psychological assessments were conducted by trained nurses. Details of the baseline evaluations were described previously (Nishiwaki et al 2005). …”
Section: Measurements At the Baseline Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological assessments were conducted by trained nurses. Details of the baseline evaluations were described previously (Nishiwaki et al 2005). …”
Section: Measurements At the Baseline Examinationmentioning
confidence: 99%
“…To address this issue, we initiated the Yamato Study, a population-based study of individuals utilizing the long term care service system, to develop preventive methods for diminishing ADL levels (Nishiwaki et al 2005(Nishiwaki et al , 2007.…”
mentioning
confidence: 99%
“…Details of the methods used to obtain these measurements were described previously (Nishiwaki et al 2005).…”
Section: Measurementsmentioning
confidence: 99%
“…As for mobility, dependency was most severe with respect to standing up from a sitting position, standing on one foot, sitting up in bed, walking, maintaining a sitting position, turning over in bed, and standing on both feet. Nishiwaki et al (2005) studied subjects who required low levels of care, and noted that there was a significant increase in the dependence level for bathing and using stairs. In the present study, we found increased dependence in standing up from a sitting position and standing on one foot in the earlier stages of disability.…”
Section: Discussionmentioning
confidence: 99%